THE ACTIVITY APPROACH AS A BASIS FOR PRESCHOOL TEACHERS' METHODOLOGICAL ACTIVITIES - Aleksieienko-Lemovska, L.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article analyzes the content of the activity component of the methodological competence of the teachers of pre-school educational institutions in the system of continuous education and noted that the activity approach provides the opportunity to develop holistic integration models as well as to identify basic functions, elements, components, their relationships and interconnections, system-forming factors and the functioning conditions in static and dynamic aspects. All professional competence structural components are aimed at the preschool teacher`s practical activity, in particular, the capacity for solving specific pedagogical situations. The objectives of methodological competence development in preschool teachers are achieved in the process of professional training and retraining, the improvement of methodological tools for methodological work. The activity approach is the basis of preschool teachers` methodological activities and should ensure the formation of readiness for self-development and continuing education, modelling and construction of social environment for personal development in the education system, active cognitive activity. The principles of methodological work organization: relevance, unity of theory and practice; scientific character to the conformity with modern scientific achievements in various fields; the unity and interconnection of all directions of teachers` professional development; goal orientation, consistency, succession, a mass character, and collectivity; the methodological work transformation into a part of the continuing education system, teachers engagement into various forms of methodological; creation of favorable working conditions, the availability of free time for the teacher's creative activity; efficiency, flexibility, mobility and an individual approach requiring, the creative nature of methodological work, the creation of a methodological work system in a preschool institution; continuing teachers` self-education, qualified assistance provision both in theoretical and in practical matters; improving teaching effectiveness.